2006
DOI: 10.1002/adem.200500276
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Characterization of Unmodified and Sr‐Modified Al‐Si Eutectics by FIB and FIB EDX Tomography

Abstract: The starting materials are high purity metals: Zr (99.6 %), Cu (99.999 %), Al (99.999 %), Nb (99.995 %), and Ni (99.995 %). Two steps are used for the preparation of master alloys. First, the binary solid-solution ingots of Zr-Nb are fabricated. Second, Zr-Nb ingots are arc melted into master alloy with the remaining elemental components, such as Ni, Cu, and Al. For each step, the ingot is melted and flipped 5 times for total about 8 min. Then, the bulk metallic glass of the nominal composition of (Zr 58 Ni 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“…The unmodified plate-like eutectic Si phase presents a much coarser structure in comparison to the Srmodified eutectic. Although Figure 1(b) depicts small rounded disconnected particles in the transversal section, the three-dimensional structure consists of an interconnected corallinelike architecture [23].…”
Section: Methodsmentioning
confidence: 99%
“…The unmodified plate-like eutectic Si phase presents a much coarser structure in comparison to the Srmodified eutectic. Although Figure 1(b) depicts small rounded disconnected particles in the transversal section, the three-dimensional structure consists of an interconnected corallinelike architecture [23].…”
Section: Methodsmentioning
confidence: 99%
“…Focused ion beam tomography has recently been used by Lasagni et al [192] for high-resolution investigation of the 3D structure of Sr-modified and unmodified Al-Si alloys (Fig. 10), and volume-based structural parameters have been used to identify the flake/fiber transition, which is not indicated through conventional spacing measurements [193].…”
Section: Irregular Eutectic Growthmentioning
confidence: 99%
“…In Al-Si alloys, there is a strong relationship between morphology of eutectic Si and their mechanical properties. Commercially used modification of the microstructure morphology with Sr addition changes the morphology of Si from a coarse plate-like into refined fibrous structure, significantly improving mechanical properties of the alloy, particularly tensile strength and elongation [2,3,4,5,6]. The results reported by Shin et al [6] have shown that Sr-modification of Al-10.5Si-2.0Cu recycled alloy leads to an increase of the elongation by a factor of two (from 2.0 to 4.1%) and tensile strength by more than 10% (from 209 to 237 MPa), which is reflected by a higher quality index of the material.…”
Section: Introductionmentioning
confidence: 99%